Nipple Skin Sparing Mastectomy and Immediate Reconstruction with implant using Acellular Dermal Matrix (ADM)in a Patient with TP53 mutation - First Experience in Bangladesh - Ahmed, SK Farid; Nafisa, Ali; Priam, Samanta Meharin; Ferdous, Hasnatul; Rahman, ASM Tanjilur; Khan, Md Salim; Riad, Mahedi Hassan (Journal of Surgical Sciences, 2021)
A 28-year-old lady presented with 3.5 cm lump in her right breast and normal axilla. Histopathologically the lump revealed as invasive duct cell cancer (IDC), Grade II with ER negative, PR positive and HER2 equivocal. On genetic testing, BRCA1 & BRCA2were found negative but p53 was positive with pathogenic variant. She received neoadjuvant chemotherapy while waiting for genetic testing. As she had TP53 mutation and considered high risk for developing contralateral breast cancer, bilateral mastectomy and immediate reconstruction with implant using acellular dermal matrix was performed on 9th of March,2020 at our Breast Unit during 2nd live surgery & workshop on oncoplastic breast surgery, organized by Breast Care Unit and Research Centre, Department of Surgery, Anwer Khan Modern Medical college. This is the first reported case of a breast cancer patient with TP53 mutation who has undergone nipple skin sparing mastectomy with immediate implant/ADM reconstruction and creates a milestone in the history of modern breast cancer management in Bangladesh. Journal of Surgical Sciences (2020) Vol. 24 (2) : 77-82